The Mobile Revolution: Understanding the Impact of Mobile Apps on Consumer Behavior - Ionela-Lidia Beldean (Ovidius University Annals: Economic Sciences Series)
Mobile applications have transformed the landscape of consumer behavior, embedding themselves as critical tools in modern marketing strategies. This study explores the intersection of mobile app marketing and consumer experiences, examining its effects on decision-making processes and brand engagement. Through a comprehensive review of the literature, we analyze the enablers and barriers presented by mobile platforms, highlighting their role in shaping the customer journey. Insights derived from this investigation provide actionable recommendations for marketers and app developers to enhance user satisfaction and trust, ensuring sustained engagement in an increasingly digital economy.